Scarring or scaring?: the psychological impact of past unemployment and future unemployment risk - Andreas Knabe; Steffen Rätzel (Center for Economic Studies and ifo Institute (CESifo), 2008)
We reassess the scarring hypothesis by Clark et al. (2001), which states that unemployment experienced in the past reduces a person's current life satisfaction even after the person has become reemployed. Our results suggest that the scar from past unemployment operates via worsened expectations of becoming unemployed in the future, and that it is future insecurity that makes people unhappy. Hence, the terminology should be altered by one letter: past unemployment scars because it scares.
Keywords: I31; D10; J60; 330; Unemployment; scarring; happiness; life satisfaction; Arbeitslosigkeit; Risiko; Erwartungstheorie; Lebenszufriedenheit; Deutschland